PENGEMBANGAN MODIFIKASI BOLA PLASTIK TERHADAP PENINGKATAN KETERAMPILAN PASSING ATAS BOLA VOLI PADA SISWA KELAS VIII E SMP NEGERI 13 SURABAYA - PURBOJO, SUTO (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract To improve the quality of teaching physical education, sport and health, required an alternative to the use of methods, strategies, and media relevant learning and flexible learning materials. Special to the material passing the volleyball learning, many students at Junior High School 13 Surabaya encounter in doing so. It required a modification of instructional media such as the use of spherical modifications to improve it. In this study, the authors wanted to answer the problem: "What is the use of spherical modifications can improve the ability of passing the volleyball on the learning of physical education and health?" Action research conducted in the eighth grade students of SMP Negeri 13 E Surabaya school year 2012/2013. The planned cycle there are 2 phases, the first cycle and second cycle. Data collection is done by passing the test using real volleyball. Descriptive data were analyzed qualitatively and visualized in tabular form to facilitate reading of the results. Hypothesis actions and findings are: Ball modifications can improve the ability of passing the volleyball on the learning of physical education, sport, and health in class VIII E SMP Negeri 13 Surabaya. Keywords : Modification, Volley Ball Upper Pass